Competencies in edible insects production for training of vocational agricultural education students in Kogi State - Ojonugwa, Alexander; Mohd Puad, Mohd Hazwan; Omar, Muhd Khaizer; Mohd Sufian Kang, Enio Kang; Joy, Yahaya (Macrothink Institute, 2022)
In an effort to meet up with animal nutrient shortfall and ever increasing human populacewhile managing the attendant health challenges of meat consumption, various unconventional sources of nutrients, exceptionally micro-livestock, has been recommended to form integral part of the nation’s traditional farming system and consumption. Therefore, the farming and consumption of edible insects are seen as an essential tool in improving the animal nutrient supply in the country. This study therefore aimed at identifying the competencies required in the production of edible insects to train the students of Vocational Agricultural Education (VAE) for considerable economic empowerment post graduation. This study adopted a survey research design implemented on a population of 104 respondents. It was found that VAE students required all the competencies identified in the entomological literacy, housing, planning, and maintenance of edible insects for economic empowerment psotgraduation. The finding of the test of hypotheses showed no significant difference (p>0.05) in the respondents’ mean responses on the entomological literacy, housing, planning, and maintenance competencies needed in the production of edible insects. From this findings, it was therefore recommended that all the identified competencies of edible insect production be applied in the training of VAE students.